Evaluating Interaction Between Inflation and A Composite Macroeconomics Index - Mauto, Respect Kudzai; Jeke, Leward; Mukarati, Julius; Abel, Sanderson (International Journal of Economics and Financial Issues, 2025)
This empirical investigation endeavours to elucidate the causal nexus between inflation and the dynamic confluence of money supply, interest rates, and GDP growth rate in five select African countries, leveraging annual panel data spanning the period from 2010 to 2024. Utilizing a Vector Error Correction Model (VECM) estimation paradigm, the results unveil a statistically significant long-run relationship between inflation and the Money supply-interest rate-GDP growth rate index (MIG Index). However, the MIG Index fails to Granger-cause inflation, suggesting that fluctuations in these macroeconomic variables do not exert a statistically significant long-run impact on inflation. This finding highlights the intricate interplay between inflation and macroeconomic variables, underscoring the substantial impact of inflationary pressures on salient economic indicators. The study’s findings possess significant implications for policy decisions, emphasizing the imperative of mitigating potential macroeconomic instability. By grasping the long-run relationship between inflation and MIG, policymakers can devise targeted strategies to manage inflation and promote economic stability. Furthermore, the results underscore the importance of considering the autoregressive nature of inflation and the impact of past inflation levels on macroeconomic variables.